Studi Literatur: Analisis Pengetahuan dan Sikap Mahasiswa Farmasi dalam Pembuangan Limbah Obat dengan Perspektif Ekofarmakologi - Shalum Putriyani; Indah Laily Hilmi; Devi Ratnasari (Jurnal Sehat Mandiri, 2025)
This literature study aims to evaluate pharmacy students' knowledge and attitudes regarding pharmaceutical waste disposal from an ecopharmacology perspective. Ecopharmacology is a branch of science that examines the environmental impact of drug residues, particularly how pharmaceutical compounds affect ecosystems after disposal. This perspective is important because unused or improperly discarded medications can contaminate water and soil, and disrupt ecological balance. The study employs a qualitative literature review method by analyzing articles from the PubMed and Scopus databases over the past ten years. The results show that although pharmacy students possess basic knowledge about the environmental risks of improper drug disposal, there remains a gap in practical application. Ecopharmacology education has proven to play a significant role in raising awareness and fostering environmentally responsible attitudes. Conclusion: Pharmacy students have basic knowledge about the environmental impact of drug disposal, but its implementation is still suboptimal.Recommendation: It is recommended to integrate ecopharmacology into the pharmacy curriculum and provide proper and easily accessible pharmaceutical waste disposal facilities.